Exploring the actual implementation of e-wallet application in Malaysia (Baghdad Science Journal, 2024)
E-wallet, also referred to as digital wallet, is a software application designed to replace physical wallets, with the primary purpose of facilitating online transactions when users wish to make virtual payments. Nowadays, E-wallets are not limited to mobile applications, but they have also been extended to wearable devices, such as smartwatches, enabling users to make payments via their watches. This research study focuses on three main E-wallet service providers in Malaysia, namely TouchNGo E-wallet, Boost, and Grab pay, as they are the top three E-wallets in the country. The aim of this paper is to explore the real-world implementation of E-wallets among mobile phone users in Malaysia, employing the Technology Adoption Model as the theoretical framework. Six independent variables were identified to study the implementation of E-wallets, and a total of 500 respondents shared their opinions on retaining the usage of E-wallet in Malaysia. The data collected were analysed using SPSS for Pearson Correlation Analysis and Multiple Linear Regression. Out of the six variables, five independent variables were accepted, and one independent variable was rejected due to the greater significant level. The highest correlation coefficient falls under Business Resources with 0.704. The study delves into the implications and constraints, providing insights for the future advancement of E-wallets within the Malaysian context.